Analysis of Students Perception in Reading Comprehension of English Texts at Junior High School: Analisis Persepsi Siswa dalam Pemahaman Membaca Teks Berbahasa Inggris di SMP - Dwi Pundi Lestari; Dian Novita (Universitas Muhammadiyah Sidoarjo, 2022)
The purpose of this study was to identify the difficulties faced by students in reading comprehension of English texts and to identify the factors causing students' difficulties in understanding reading English texts in class VIII-B students of SMP Muhammadiyah 9 Boarding School. This research is qualitative. Data collection techniques used are tests and interviews. This study uses data analysis techniques from Miles and Huberman (1992), there are three steps of data analysis, namely data reduction, data display, and drawing conclusions. Based on the research results, students have difficulty in determining the main idea, understanding vocabulary, making conclusions, and looking for detailed information. The results of interviews regarding the factors that cause students' difficulties in understanding English reading texts are difficulties in understanding long sentences in the text, inadequate teacher intervention, and difficulties in understanding vocabulary, the home environment, and the school environment.